Commodity exchanges and warehouse receipts in Malawi: Current status and their implications for the development of structured markets - Baulch, Bob; Gross, Adam; Nkhoma, Justice Chimgonda; Mtemwa, Chikumbutso (International Food Policy Research Institute, 2018)
This study examines the landscape in which Malawi’s two agricultural commodity exchanges (Comex) and warehouse receipts systems (WRS) operate and makes recommendations on how to improve their performance and benefits to key stakeholders. A mixed methods approach was adopted, involving semi-structured interviews with key market participants, compilation and analysis of secondary data from Malawi and other African Comex, and a review of existing literature. A review of international experience indicates that historically Comex often develop hand-in-hand with warehouse receipt systems (WRS), which help stimulate demand from off takers for standardized contracts while providing financing that increased volumes traded. In recent years, electronic trading platforms have given an impetus to the consolidation of existing Comex, and the development of regional networks of exchanges and warehousing arrangements. Nonetheless, a common reason why Comex fail is that they do no attract sufficient trading volumes to pay for their operating costs. This is often associated with default on contracts and fears of the market for commodities being cornered by a few larger traders. Of the 23 Comex in Africa, over half are still in their planning or inception stages and, with the notable exception of the agricultural futures and options traded on the Johannesburg Stock Exchange, most of the remaining Comex are thinly traded and receive financial support from government and/or donors.